Perancangan Pengasutan Bintang – Segitiga dan Pengereman Dinamik pada Motor Induksi 3 Fasa dengan Menggunakan Programmable Logic Controller (PLC) - Prakoso, Isna Joko; Warsito, Agung; Sukmadi, Tejo (Transmisi, 2012)
Three-phase induction motor is the motor of alternating current (AC) is the most widely used and much used by the industry because it has several advantages, among others, this motor is simple, in expensive and easy to maintain and can be directly connected to an AC power source. Besides the advantages of this motor, also has disadvantages. The disadvantage of this induction motor which has a large starting currents and the use of induction motors are often needed to stop the motor rotation quickly, especially for conveyor applications. At this final project, created a system starting star (Y)-triangle (Δ) and the dynamic braking of three phase induction motor using a Programmable Logic Controller (PLC). Where the system is very simple, does not require a lot of support tools and can be applied to any type of three-phase induction motors. Starting of the test results to show that the method starting with Y-Δ has a starting current of 3.59 A. This current is smaller than the nominal starting current induction motor 1 HP is 6.3 A relationship Δ and 3.62 A relationships Y. Starting time is good for the displacement of the star (Y) - triangle (Δ) is 6 seconds, so the starting of induction motors using the star (Y) - triangle (Δ) can reduce the high current flow starting of induction motor starts to operate. For braking, DC injection current is supplied by 1.908 A and the stop time for load 100 W is 1,57 seconds, for load 200 W is 1,38 seconds, and for load 300 W is 0,95 seconds. Time stopped by dynamic braking faster than without dynamic braking. Keywords : Starting star (Y)-triangle (Δ), dynamic braking, three-phase induction motor, Programmable Logic Control (PLC)